PENGEMBANGAN MODUL TEMATIK BERBASIS INKUIRI PADA TEMA 2 SELALU BERHEMAT ENERGI SUBTEMA 2 MANFAAT ENERGI KELAS IV SD/MI - Astuti, Nindi Widi; Astuti, Mardiah; Sofyan, Fuaddilah Ali (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2022)
Education is a very important requirement in improving the quality of human resources. Through education, humans can find new things that can be developed and obtained to face the challenges that exist in accordance with the times. The national education system must always be developed in accordance with the needs and developments that occur at the local, national and global levels. Based on the description of the background above, the author will conduct research with the title